Just multiply the bases and add up the exponents.
9c^6*3c^6 = 27c^6+6 = 27c^12 <- answer
You would multiply both and then the answer you would put into ratio form
One example is if you wanted to measure the height of a tall building. You'll need to measure the distance from where you're standing to the base of the building. You'll also need the angle of elevation. To get the angle of elevation, start by looking completely horizontal, then tilt upward until your eyeline reaches the top of the building. Once you have those two things (the side and angle) you can use the tangent ratio to find the height. This is because
tan(angle) = opposite/adjacent
where in this case
angle = angle of elevation
opposite = height of building
adjacent = distance from your position to the base of the building
It takes a bit of algebra, but the opposite side can be solved for. You'll most likely need a calculator to compute the tangent ratio.
Answer:
Full question attached below.
Yes, the system of equations on line 4 has the same solution set as the system of equations on line 1
Step-by-step explanation:
There is no difference between the systems of line 1 and 4
1st system
5x + 3y = 14
4x - 2y = -2
4th system
10x + 6y = 28
12x - 6y = -6
In the fourth system, we factor number 2 from the first line, and number 3 from the second line
4th system
2[5x + 3y] = 2[14]
3[4x - 2y] = 3[-2]
If we simplify,
4th system
[5x + 3y] = [14]
[4x - 2y] = [-2]
We get the same system as the 1st
Therefore, the solution is the same.